Medicinal Biospecificity of Ginger and Its Efficacious Bioactive Compounds in the Context of Its Biological Activities Against Predominant Health Issues: Current Study and New Avenues - Haseeba Shahzad; Shaifa Saleem; Waqas Hanif; Zareena Ali; Muhammad Zeeshan Ahmed; Haq Nawaz; Zelle Humma; Laraib Rana; Muhammad Qamar Farid; Hajira Kalsoom; Samavia Jaan (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
There is a multitude of life-threatening and widespread health issues worldwide, regarding weak immunity, severe inflammation, viral infections, bacterial infections as well as antimicrobial resistance (AMR), high free radicals generation, and cancer. Ginger, a perennial plant of the Zingiberaceae family with several authentic nutritional and medicinal values used in many countries as traditional medicine. That is why, the study was designed to highlight recent studies about medicinally most efficacious bio-active compounds of ginger along their biological significance related to immuno-stimulatory, anti-inflammatory, anti-viral, anti-bacterial, anti-oxidant, and anti-cancer effects. Our study also recognized future gaps in research. The study included professional research data under duration from 2001-2022 appearing in books and scholarly journals, collected from scientific database platforms via PubMed, Web of Science, Google Scholar, Springer Nature, Science Direct and Scopus. The present study includes the medicinal effects of almost 44 most influential ginger compounds like phenolics, terpenoids, flavonoids, and vinyllyl ketonic compounds etc. Our results revealed the strong alleviating effects of gingerols, shogaols, paradols, and polyphenols. Moreover, the ginger essential oil has proven to be very effective both for antiviral and antibacterial activity. However, no data is available in previous literature for components of ginger involved in immuno-stimulatory, effects. There is also a need to explore components for antibacterial activity. However, research has been conducted on ginger for only a few viruses despite its strong alleviating effects. Besides this, more study is needed to comprehend the comprehensive mechanism of action (especially at the molecular level) regarding the anti-bacterial and anti-viral activity of ginger and its constituents.